In vitro production of Kaempferia galanga (L.)- an endangered medicinal plant - M. Anbazhagan, M. Kalpana (Journal of Phytology, 2009)
Kaempferia galanga is an important medicinal plant that is facing threat of extinction owing to indiscriminate and unsustainable harvesting in the wild. Conventional breeding is difficult in this plant, and in vitro multiplication is important to conservation and propagation. Tissue culture techniques are useful for ex situ conservation of rare, endemic or threatened plant species. An efficient protocol has been established for rapid production of plantlets using rhizome tip and lateral bud of the pot cultured plant. The explants were cultured on MS medium with various combinations of 6-benzyladenine (BA), ÃŽÂ±-naphthalene acetic acid (NAA), indole-3-butric acid (IBA) and indole-3-acetic acid (IAA) at concentrations ranging from 0.1 to 3.0 mg/l. High-frequency organogenesis and multiple shoot regeneration were induced from rhizome explants on MS medium supplemented with 2.0 mg/l of BA and 0.2 mg/l of NAA. Micro-shoots were isolated from the in vitro proliferated cluster of shoots and they produced roots on half strength MS medium supplemented with 1.0 mg/l of IBA. The regenerated plantlets were transferred to plastic pots for hardening in a mixture containing red soil, sand and vermiculate(1:1:1) ratio and established on the soil with 81% of success.